Palladium/Norbornene-Cocatalyzed Three-Component Synthesis of ortho-Acylated Benzonitriles - Wang, Liqin; Song, Guangjun; Wu, Qiufang; Qin, Jiaxin; Yu, Xinhong; Chen, Niangen; Li, Cuiqing (Synthesis, 2022)
A palladium/norbornene-cocatalyzed Catellani-type ortho-C–H-acylation/ipso-cyanation of iodoarenes is developed via a three-component approach using safe and low-toxic sodium carboxylates as the acyl sources and CuCN as the CN source, affording the desired products in yields of 50–94%. Without introducing a directing group on the substrate, a catalytic amount of norbornene and palladium can regioselectively activate the ortho-C–H bonds of iodoarenes. The reaction exhibits good functional group tolerance and works well on gram-scale. In addition, this transformation allows rapid and convenient access toward isoindolinones, 1,4-dicarbonyl compounds and ortho-aminated benzonitriles by manipulation of the cyano and carbonyl groups.
Keywords: palladium; C–H activation; acylation; arenes; synthetic methods